A cross-sectional assessment of obesity among medical students of central India - Arpit Verma; Shweta Chauhan; Akanksha Lazarus; Saket Kale (Asian Journal of Medical Sciences, 2024)
Background: Obesity is one of the leading public health problems, emerging and evolving across the ages from childhood, adolescence, young adults, and middle age to the geriatric sphere of life. The young adult age group also includes the special population of medical students with possible unique stressors and risk factors requiring special attention. Aims and Objectives: The current study was planned with the objectives of studying obesity among medical students with a focus on determining the prevalence of obesity problem and associated socioeconomic level and lifestyle variables; dietary calorie intake and physical activity. Materials and Methods: The current study is a cross-sectional survey conducted using a pre-tested, semi-structured questionnaire among MBBS students of central India. A total of 400 students were interviewed. Body mass index (BMI) was used to identify and the World Health Organization classification (WHO) was used to categorize the students in nutritional levels. Physical activity level was assessed using the General Practice Physical Activity Questionnaire. Socioeconomic status (SES) was assessed using the Modified Prasad Classification and All India Consumer Price Index. Dietary calorie intake was assessed using 24-h oral questionnaire method. Results: The current study finds a prevalence of 7.5% obesity among medical students with another 10% in the pre-obese category as per the WHO classification. It was also found that Male gender, inactivity, and upper SES were significantly associated with the obesity prevailing in this special population of medical students. Conclusion: The current study concludes that obesity/pre-obesity is an important problem prevalent among medical students with association with sedentary lifestyle and high SES; thus, recommends screening students for lifestyle disease, dietary modification, change in sedentary lifestyle, and recreational activities to reduce stress.